THE DECISION MATRIX OF THE MOST EFFICIENT ENERGY UTILIZATION FOR COLD STORAGE AT PULAU MOROTAI REGENCY - Yoesgiantoro, Donny (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Pulau Morotai Regency is one of the areas identified by the government as a fisheries-focused Special Economic Zone. However, the reality on the ground is that the fishing industry has only one cold storage facility. One of the factors is the region's remote position, which requires a considerable amount of capital and operational expenditure. Lower energy costs are one way to reduce the operating cost. This study aims to determine the value of each energy-efficient criterion and to know the most efficient energy composition implemented for Cold Storage in Morotai. This study uses the decision matrix approach to compare the operating costs of cold storage with a capacity of 200 tons over 20 years with three possible alternatives: PLN electricity, hybrid electricity (PLN + photovoltaic), and fully photovoltaic energy. With a score of 38 in the decision matrix table, the outcome of the decision matrix calculation indicates that cold storage with a photovoltaic system is much superior.